Researchers’ information needs in the bibliographic database: a literature review - Andrade, Morgana (2014)
This article presents a literature review whose aim was to identify the reported information needs of researchers when they consult bibliographic databases. Initially, 192 articles were retrieved using Scopus, Web of Science and Google Scholar databases. After applying the criteria for exclusion, the number of articles was reduced to 16, which is already an indicator of the small number of studies on this specific topic. The results show that it is hard to identify the information needs of researchers. They also show that the researchers have been requiring information with a higher degree of granularity. We conclude that although the available studies provide important information about the researchers’ information needs and hints on how to address them, there is a need for more in-depth studies. The results of these deeper studies may be useful to serve as an indication for the creation of new procedures and tools, including those based on new metadata elements drawn to improve search results on Linked Open Data tools.